The European Discovery of the Indian Flora - Desmond Ray (Oxford University Press Oxford, 1992)
The flora of the Indian subcontinent has stirred European curiosity and investigation for over two millennia. From pepper, a coveted commodity of the lucrative spice trade, to rhododendrons, orchids, and alpine flowers, cherished in innumerable British gardens and conservatories, Indian plants have long been highly prized in the West. This book surveys European perceptions of the diversity of the Indian flora, and examines its impact on European commerce and culture including botany, horticulture, and floral art. It chronicles the growing European awareness of the Indian flora from the first glimmerings of knowledge in the fifth century BC to the demise in the mid-nineteenth century of the British East India Company and of its successor, the India Office. An epilogue briefly surveys the development of botanical studies since the independence of India and Pakistan in 1947. The evolution of European-style gardens in India is examined, and the impact of the Indian flora on British gardens is assessed.
Includes bibliographical references and index
Keywords: Gardens -- European - Indic influences; Botany -- Hisory -- India